Development and validation of a UHPLC-QqQ-MS/MS method for simultaneous determination of fifteen major components from Oroxyli seed extract in rat plasma and its application in the pharmacokinetic study - Lv, Zhenguo; Zhang, Kaili; Zhang, Zijing; Ma, Jinyue; Li, Wenwen; Chen, Lu; Lin, Wenhan; Zhu, Yameng; Ge, Minglei; Ouyang, Huizi; He, Jun (Frontiers in Pharmacology, 2025)
For this investigation, a UHPLC-QqQ-MS/MS method was developed for the simultaneous determination of 15 components (chrysin, chrysin-7-O-β-D-glucuronide, hispidulin, wogonoside, quercetin, quercetin-7-O-β-D-glucoside, baicalin, baicalein, acacetin, oroxin A, oroxin B, oroxylin A, oroxylin A-7-O-β-D-glucuronide, apigenin, and scutellarein) in rat plasma. An ACQUITY UPLC BEH C18 column was utilized for separation, and simultaneous detection of the analytes was achieved through the multiple reaction monitoring mode. Method validation results were all within acceptable ranges for biological sample determination. Subsequently, the method was applied to pharmacokinetic studies in rats following oral administration of Oroxyli seed (OS) extract. The results indicated that baicalin, oroxylin A, and oroxylin A-7-O-β-D-glucuronide exhibited significant bimodal phenomena. The maximum concentration of baicalin was 13376.96 ± 2232.32 ng/mL, indicating a relatively high blood concentration. This may be related to the high content of oroxin A and oroxin B in OS extract being metabolized to baicalin. The present study may provide guidance for the further application of OS.